PREDICTION OF RENAL FLARE IN ADULT PATIENTS WITH LUPUS INDUCED NEPHRITIS - Batool, Hijab; Naseem, Tahira; Shoukat, Marium (Journal of Ayub Medical College Abbottabad, 2021)
Background: The most common complication of SLE is lupus nephritis (LN) causing high morbidity and mortality. The routine biomarkers used for the diagnosis of LN do not have the ability to predict the worsening in renal disease activity. Thus, there is need of a new biomarker leading to detection of flare in LN. The objective of this study was to assess the role of urinary neutrophil gelatinase associated lipocalin (uNGAL) as a predictor of renal flare in patients with lupus nephritis. Methods: Including a total of 84 subjects, 42 cases were lupus patients without renal involvement and 42 cases were lupus patients with nephritis (24 active nephritis and 18 inactive nephritis). The diagnosis of lupus nephritis was established on the basis of renal biopsy. uNGAL was estimated in both groups. Results: This study revealed that the nephritis group had increased levels of uNGAL as compared to systemic erythematosus patients without having lupus nephritis (p-value <0.05). Patients with active nephritis had increased uNGAL levels as compared to patients with inactive nephritis. Conclusion: From the findings in our study, it can be stated that uNGAL can prove to be a noninvasive, reliable and sensitive biomarker to predict flare in cases of lupus nephritis. Keywords: Neutrophil Gelatinase Associated Lipocalin; systemic lupus erythematosus; Lupus nephritis; Biomarker; Renal Disease Activity; Flare